Rapid detection assay of toxigenic Clostridioides difficile through PathOC RightGene, a novel high-speed polymerase chain reaction device - Okanda, Takashi; Mitsutake, Hiroshi; Aso, Ryoko; Sekizawa, Ryuichi; Takemura, Hiromu; Matsumoto, Tetsuya; Nakamura, Shigeki (Diagnostic Microbiology and Infectious Disease, 2021)
Nucleic acid amplification tests for diagnosing Clostridioides difficile infections (CDI) are improving to become faster and more accurate. This study aimed to evaluate the accuracy of rapid detection of toxigenic C. difficile using the novel high-speed polymerase chain reaction (PCR) device, PathOC RightGene. These results were compared and evaluated with real-time PCR (qPCR) and enzyme immunoassays (EIA) kit. For this study, 102 C. difficile and 3 Clostridium species isolated from CDI patients were used. These C. difficile isolates were 85 toxigenic and 17 non-toxigenic strains. The results of qPCR served as a standard, and sensitivity, specificity, positive predictive value, negative predictive value, and accuracy of the PathOC Right Gene were 99.2%, 99.4%, 100%, 98.8%, and 99.3%, respectively. Turnaround time of qPCR and EIA was 85 and 30 minutes, whereas PathOC RightGene was only 25 minutes including DNA extraction. This novel high-speed PCR device detected toxigenic C. difficile rapidly and accurately.